META-ANALYSIS : COMPARISON OF NEOVAGINA SUCCESS RATE WITH VECCHIETTI'S LAPAROSCOPIC METHOD AND DAVYDOV'S LAPAROSCOPIC METHOD IN MAYER-ROKITANSKY-KUSTER-HAUSER SYNDROME (MRKH) PATIENTS - Yanuar Prionggo; Eighty Mardiyan Kurniawati (Jurnal Ilmu Kesehatan dan Kesehatan, 2020)
Background: Mayer-Rokitansky-Kuster-Hauser Syndrome (MRKH) is caused by an embryological growth disorder of the mullerian duct. Laparoscopic Vecchietti and Davydov are laparoscopic surgery techniques that are often used for neovaginal surgery Objective: This paper aims to compare the success rate of neovagina with the Vecchietti laparoscopic method and Davydov's laparoscopic method in patients with Mayer-Rokitansky-Kuster-Hauser Syndrome (MRKH) Methods: A systematic data search was performed on a medical database (PUBMED, MEDLINE, Cochrane Database, Google Scholar). Inclusion criteria: (1) randomized randomized study of the Vecchietti Laparoscopic Method with Davydov’s Laparoscopy, (2) all inclusive papers can be accessed completely, and (3) the data obtained can be accurately analyzed Data acquisition and analysis: We searched for a random blind study (RCT) with the following keywords: (1) Vecchietti Laparoscopy [title] AND (2) Davydov’s Laparoscopy [title] AND Mayer-Rokitansky-Kuster-Hauser syndrome [title] Results: Three RCTs comparing neovaginal success with the Vecchietti laparoscopic method and Davydov's laparoscopic method a total of 122 patients were analyzed. Average vaginal length (mean difference [MD] -0.70, and 95% [CI] -0.99 to -0.41 (P <0.00001), Average number of Female Sexual Function Index scores (mean difference [MD] -1.34, and 95% [CI] -1.71 through -0.96. (P <0.00001) Conclusion: This meta-analysis concludes that Davydov’s Laparoscopic Method is better in terms of postoperative vaginal length and the Female Sexual Function Index Score